Parental obesity-induced changes in developmental programming - Cechinel, Laura R.; Batabyal, Rachael A.; Freishtat, Robert J.; Zohn, Irene E. (Frontiers in Cell and Developmental Biology, 2022)
A plethora of studies supports the link between parental obesity and the predisposition to develop adult-onset metabolic syndromes that includes obesity, high blood pressure, dyslipidemia, insulin resistance, and diabetes in the offspring. As the prevalence of obesity increases in persons of childbearing age, so does metabolic syndrome in their descendants. Understanding how parental obesity alters metabolic programs in the progeny, predisposing them to adult-onset metabolic syndrome, is key to breaking this cycle. This review explores the basis for altered metabolism of offspring exposed to overnutrition by focusing on critical developmental processes influenced by parental obesity. We draw from human and animal model studies, highlighting the adaptations in metabolism that occur during normal pregnancy that become maladaptive with obesity. Furthermore, we describe essential phases of development impacted by parental obesity that contribute to long-term alterations in metabolism in the offspring. These encompass gamete formation, placentation, adipogenesis, development of the pancreas, and appetite control circuits in the brain. Parental obesity alters the developmental programming of these organs in part by inducing epigenetic changes with long-term consequences on metabolism. While exposure to parental obesity during any of these phases is sufficient to alter metabolism long-term, most often, offspring experience multiple exposures throughout their development that accumulate to increase further the susceptibility of the offspring to the obesogenic environments of modern society.